2014
DOI: 10.1177/1357633x14555610
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of telemedicine for post-operative urological care in children

Abstract: We conducted a retrospective study of paediatric urological surgery patients over a 12-month period. We compared patients followed up by telemedicine with those who had post-operative follow-up on site at the Arkansas Children's Hospital (ACH) in Little Rock. All pre-operative patients living in northwest Arkansas were given the opportunity to use telemedicine from a satellite clinic at Lowell, 328 km from the hospital. Of 61 patients, 10 chose telemedicine and 51 chose to be evaluated at the ACH clinic. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 8 publications
2
76
0
1
Order By: Relevance
“…56,57 Seven studies examined the potential for replacing follow-up clinic visits with a telephone call 47,54 or an online videoconference, either from the patient’s home 45,48,49 or from an affiliated remote clinic site. 50,52,53 Among the studies using telemedicine for ongoing monitoring, patients’ reported symptoms were collected either by automated telephone survey 43 or videophone with live patient interviews. 51 Specific objective clinical data were collected using text messages for daily surgical drain output, 55 electronic transmission of home spirometry results, 58 and more complex multi-modal monitoring of symptoms, blood pressure, and medication adherence.…”
Section: Resultsmentioning
confidence: 99%
“…56,57 Seven studies examined the potential for replacing follow-up clinic visits with a telephone call 47,54 or an online videoconference, either from the patient’s home 45,48,49 or from an affiliated remote clinic site. 50,52,53 Among the studies using telemedicine for ongoing monitoring, patients’ reported symptoms were collected either by automated telephone survey 43 or videophone with live patient interviews. 51 Specific objective clinical data were collected using text messages for daily surgical drain output, 55 electronic transmission of home spirometry results, 58 and more complex multi-modal monitoring of symptoms, blood pressure, and medication adherence.…”
Section: Resultsmentioning
confidence: 99%
“…8 Urological telemedicine has been studied in a small number of pediatric populations and has been found to provide better continuity of care by eliminating distance barriers and reducing the burden on families travelling to bring their children to more traditional appointments. 9,10 Studies in the adult population have so far been mainly limited to the application of remote telesurgery, with the advent of robotic surgical systems. 11,12 Some small, single-centre studies of the adult urological population and telemedicine in the U.S. have so far shown good patient/provider satisfaction and success.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, one of the main areas in which teleconsultation in surgery has been highly effective is the provision of pre-and postoperative care especially to rural or isolated patients. Canon et al demonstrated its feasibility even in a paediatric population following urological surgery [42]. Particularly in subspecialist areas, patients often have to travel long distances to see the surgical teams imposing a significant burden.…”
Section: Teleconsultationmentioning
confidence: 98%
“…Particularly in subspecialist areas, patients often have to travel long distances to see the surgical teams imposing a significant burden. Through their teleservice, Canon et al were able to save families an average of $88 and 2.6 h per consultation [42]. Like the email systems, other more lowtechnique systems have also been developed such as a mobile Bapp^which took over from a telephone-based follow-up service for ambulatory plastic surgery patients [43].…”
Section: Teleconsultationmentioning
confidence: 98%